Konsepsi Pemerintahan Islam Menurut Muhammad Yusuf Musa - Matosim Matosim (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2019)
The Islamic world which was formerly strong and glorious has become one of the colonies of Western nations. This unquestionably impacts many countries that they are no longer want to use Islam as a form of their government, but prefer the concept of the nation (nation-state). Even among Muslims scholars, the concept of Islamic governance is still debatable and questionable. One of the Muslim scholars who concur with the idea of the Islamic government is Muhammad Yusuf Musa, a lecturer at Al-Azhar Egypt, a graduate on Philosophy at the Faculty of Humanities at the University of Paris. This paper aims to find out Muhammad Yusuf Musa's thoughts about the Islamic government. The research found that according to Muhammad Yusuf Musa, the objectives of the Islamic government are (1) maintaining God's message on earth, and (2) improving human welfare by maintaining the unity and integrity of the people, helping each other and protecting the country from aggression and tyranny. Furthermore, the administration of the Islamic government demands two things, namely justice and shura. According to Musa, a leader must be chosen by the people, not by the appointment of the previous leader.